A study on level of understanding of people towards regular saving plan / Nurhayathy Abd Lait - Abd Lait, Nurhayathy (Faculty of Business and Management, 2009)
The objective of this paper is firstly to determine the level of understanding of people towards Regular Saving Plan, which is an investment product by CIMB Wealth Advisor. Secondly,to identify the relationship between all independent variables and people understanding towards Regular Saving Plan. Lastly to identify the most influence factor that contributes to the understanding of people towards Regular Saving Plan. The respondent of this study were among the staffs of Perodua Manufacturing Co. in Rawang, Selangor and 60 questionnaires had been distributed. The sampling method that been used is nonprobability sampling, that is snowball sampling, which is an initial group of respondents, is selected, usually at random. Subsequent respondent are selected based on the referrals or information provided by the initial respondents. This process may be carried out in waves by obtaining referrals from referrals. The independent variables are method of promotion strategy, consultant/salesperson and integrated marketing communication. After been tested, the result shows that the level of people understanding towards Regular Saving Plan is only moderate based on the mean value 0.365. while the relationship between independent and dependent variable shows that method of promotion strategy and consultant/salesperson are positive based on the significant, while integrated marketing communication is not significant, negative relationship. The most influence factor are method of promotion strategy and consultant/salesperson.